2023
DOI: 10.1007/s00520-023-07689-4
|View full text |Cite
|
Sign up to set email alerts
|

Nurse-guided patient self-treatment in integrative oncology: a randomized controlled trial

Abstract: Objective Nurses are increasingly becoming involved in integrative oncology (IO) programs. This study examined the additive effect of nurse-provided guidance for self-administered IO therapies on cancer-related fatigue and quality of life (QoL). Methods The study was randomized and controlled, enrolling patients undergoing active oncology treatment with IO interventions for fatigue and other QoL-related outcomes. IO practitioner guidance on self-treatment with manual, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…In a study on nurse-guided patient self-treatment in integrative oncology, Ben-Arye et al demonstrated symptom improvement within 24 hours of intervention as a short-term effect. 42 Many participants in the present study have experienced notable improvements in their overall well-being and specific symptoms. The offer of IN was positively evaluated by the participants: The satisfaction levels with the IN were remarkably high, with a large proportion of participants reporting a positive experience.…”
Section: Discussionmentioning
confidence: 66%
“…In a study on nurse-guided patient self-treatment in integrative oncology, Ben-Arye et al demonstrated symptom improvement within 24 hours of intervention as a short-term effect. 42 Many participants in the present study have experienced notable improvements in their overall well-being and specific symptoms. The offer of IN was positively evaluated by the participants: The satisfaction levels with the IN were remarkably high, with a large proportion of participants reporting a positive experience.…”
Section: Discussionmentioning
confidence: 66%
“…La participación de enfermería en programas de oncología integrativa está en aumento. En un estudio sobre el efecto aditivo de la orientación proporcionada por estos profesionales para las terapias de autocuidado en oncología integrativa, se encontró que esta adición redujo aún más las puntuaciones de fatiga y mejoró el apetito a corto plazo (Ben-Arye et al, 2023).…”
Section: Discussionunclassified